ВЛИЯНИЕ КУРСА ВАЛЮТ НА ЭКСПОРТНУЮ И ИМПОРТНУЮ ДЕЯТЕЛЬНОСТЬ - Нодиров Бехзод Баходирович (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The exchange rate is one of the key factors that determine the dynamics of a country's import and export operations. Currency fluctuation affects the price of goods and services on the international market and thus the competitiveness of exporters and the creditworthiness of importers. The mechanisms of the exchange rate's impact on foreign trade operations, the role of exchange rates in the formation of the trade balance, and the influence of exchange rate risks on the entrepreneurial activities are studied in the article. A special attention is paid to the strategies of currency hedging, measures of government's policy, and probable consequences of devaluation and revaluation for the economy. The analysis presented is based on theoretical research, as well as empirical data, which allows a comprehensive understanding of the issue being discussed.